The relevance of integrating multiple sensory modalities into capturing devices: the case of the global pest Sirex noctilio - Masague, Santiago; Bruchhausen, Axel; Rozas, Guillermo; De La Vega, Gerardo; Villacide, Jose Maria; Corley, Juan Carlos; Martinez, Andres (Wiley, 2024)
Sirex noctilio is an invasive forest wasp that affects pines in many parts of the globe and can result in severe economic losses. Current trapping methods for monitoring the pest rely heavily on non-specific semiochemicals. This lack of specificity can translate into low attraction/capture levels, something that is undesired, especially when the intent is to detect the pest when still at low population densities. In this context, an interesting opportunity arises to increase trap sensitivity by incorporating visual cues. For this, we evaluated potential sources of visual information that, in accordance with the ecology of the species, could elicit an attractive response complementary to the olfactory cues. We measured the reflectance spectra of pine bark, chlorotic needles and woodwasp male abdomens. The spectra were then compared with 120 commercial paint colours to be applied on panel traps. During two flight seasons, field experiments were conducted with the deployment of 155 traps, combining the volatile bait (turpentine) and different coloured traps. We observed a significantly higher number of captures towards traps with pine bark-like colourations compared with the black control traps. Our results are encouraging, as they suggest the potential of combining visual and chemical information for sustainable pest biomonitoring.